المدرسة التجريدية وأهم روادها - زريق, أحمد (مكتبة كلية الأدب العربي والفنون, 2023)
الفن شكل من أشكال العلاج "أرسطو" الفن من أهم مكونات أي حضارة عظيمة فلا تنهض دولة وتتميز إلا وجدت الفن داخلا ضمن تركيب مجتمعها، وهذا الان الفن ما هو إلا مهارة وابداع في صياغة الأمور وتشكيلها لتقدم في النهاية نتيجة مميزة ومختلفة سابقة لعصرها لهذا يعد الكثير من الفنانون أقرب منهم للجنون لأن خيالهم المنطلق هو السبب في توليد هذا الفن الراقي لذا نجد أن أعظم الفنون مازالت مستمرة وستستمر لقرون عديدة كالفن التجريدي. و لا يمكن تجاهل حقيبة أن الفن التجريدي جزء لا يتجزأ من الفنون خصوصا الفن المعاصر وفي كثير من الحالات تهيمن الحركات المختلفة التي تستخدم الأفكار المجردة وأنواع مختلفة من الفن التجريدي على الفن المعاصر ولا يمكن بل من المستحيل متابعة الفن المعاصر دون تقدير المكانة المهمة التي تحتلها الأفكار المجردة في عالم الفنون وعندما يواجه البشر فترات عصيبة من الحروب والأزمات المعيشة يصبح من الصعب تمثيل معاناتهم بشكل واقعي لهذا يلجئ الكثير لنقل مشاعره وذاكرته ونفسيته في اللوحة. فالفن التجريدي ليس شخبطات متسارعة معنى لها كما يظن البعض بل هو طريق لإخراج ما في نفوسنا وما نعيشه من ضغوطات. Art is a form of Aristotle's therapy. Art is one of the most important components of any great civilization. A country does not rise and excel unless it finds art within the structure of its society, and this now art is nothing but a skill and creativity in formulating and shaping things to provide in the end a distinct and different result ahead of its time. This is why many artists are closer to madness because their imagination is the starting point. It is the reason for the generation of this fine art, so we find that the greatest arts are still continuing and will continue for many centuries as the abstract art. The portfolio cannot be ignored that abstract art is an integral part of the arts, especially contemporary art. In many cases, different movements that use abstract ideas and different types of abstract art dominate contemporary art. It is not possible, or even impossible, to follow contemporary art without appreciating the important place that ideas occupy. Abstract in the world of arts, and when people face difficult periods of wars and crises of life, it becomes difficult to represent their suffering in a realistic way, so many resort to conveying their feelings, memory and psychology in the painting. Abstract art is not meaningless rushing scribbles, as some think, but rather a way to bring out what is in our souls and the pressures we experience.
Keywords: الفن التجريدي – الفن الحديث- المدارس الفنية – أهم الرواد; Abstract art - contemporary art - rich schools - the most important pioneers